The Influence Of The Project Based Learning Model On The Character, 21st Century Skills and Mathematics Learning Outcomes Of Class IV - Putri, Muqarramah; Supriadi, Supriadi; Maulidnawati Jumrah, Abrina (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
In initial observations in January 2024 at SDN 23 Sela, students showed a lack of enthusiasm, focus on learning and difficulty in understanding mathematical concepts. The aim of this research was to 1) find out how the project based learning model was applied to class IV students at SDN 23 Sela, Pangkep Regency 2) how the model affects student character, 21st century skills, and mathematics learning outcomes. The type of research used is pre-experimental, with quantitative research methods. This research involved 21 fourth grade students. The research instruments used were observation sheets, tests and documentation. using descriptive and inferential data analysis. The research results show that: the project based learning model is rarely used in class IV at SDN 23 Sela. This reflects recent efforts to improve character, 21st century skills and mathematics learning outcomes. Based on the results of the hypothesis test, there is a significant influence, this shows that the influence of the project-based learning model on the character, 21st century skills and mathematics learning outcomes of class IV students is significant, with a significance of 0.000 < 0.5. This means that there is a significant influence between the character-based project learning model, 21st century skills and results.